Nutraceuticals and Vitamins: A Comprehensive Guide for Naturopaths and Allied Health Professionals - Sataz Rahmania; Sangeeth Somanadhapai (Disease and Health Research: New Insights Vol. 2, 2024)
Life has become much faster due to rapid economic development and poor nutrition and food quality. As people choose junk food and processed foods, their diet becomes unbalanced and they suffer from lifestyle-related diseases that cause various health problems. The FDA defines medical food as a special type of compounded or processed food prepared for a patient, either partially or completely as the sole source of nutrition as part of the oral diet. These products are given through an enteral feeding tube to patients who are unable to absorb food orally. Their ingredients are tailored according to their nutritional benefits. Patients are being encouraged to make positive lifestyle changes as an increasing number of diseases, such as metabolic syndrome, are preventable through lifestyle changes. One of them is to change your eating habits. Dietary supplements are aimed at preventing such diseases.